2017
DOI: 10.1007/s10964-017-0773-6
|View full text |Cite
|
Sign up to set email alerts
|

Can Parenting Microprotections Buffer Against Adolescents’ Experiences of Racial Discrimination?

Abstract: Previous research highlights the importance and pervasiveness of racial discrimination for minority youth in the United States. Adolescents may experience either personal or group race-based discrimination. While past research found both forms of discrimination are harmful to well-being it is unknown whether parental microprotections, which may buffer against the negative effects of discrimination, protect against both forms of discrimination. Informed by ecological frameworks the present study examined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 52 publications
0
37
2
Order By: Relevance
“…This finding supports the proposition that racial barrier messages help to provide youth with an understanding of racial discrimination such that they are less shocked by the experience and better prepared to effectively cope (Spencer et al, 1997). In a recent study, Dotterer and James (2018) found that cultural socialization buffered racial discrimination’s effect on African American adolescents’ depressive symptoms and contrary to predictions, preparation for racial bias exacerbated the effect of racial discrimination on depressive symptoms. In addition to measuring racial socialization in general, with no defined period of time (i.e., never to very often ), Dotterer and James (2018) used parents’ reports of given messages to predict adolescent‐reported depressive symptoms “over the past week.” In that study, adolescents may have interpreted messages and behaviors differently than how parents intended, and we can only conclude how parents’ general racial socialization related to adolescents’ more recent feelings.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This finding supports the proposition that racial barrier messages help to provide youth with an understanding of racial discrimination such that they are less shocked by the experience and better prepared to effectively cope (Spencer et al, 1997). In a recent study, Dotterer and James (2018) found that cultural socialization buffered racial discrimination’s effect on African American adolescents’ depressive symptoms and contrary to predictions, preparation for racial bias exacerbated the effect of racial discrimination on depressive symptoms. In addition to measuring racial socialization in general, with no defined period of time (i.e., never to very often ), Dotterer and James (2018) used parents’ reports of given messages to predict adolescent‐reported depressive symptoms “over the past week.” In that study, adolescents may have interpreted messages and behaviors differently than how parents intended, and we can only conclude how parents’ general racial socialization related to adolescents’ more recent feelings.…”
Section: Discussionmentioning
confidence: 92%
“…Preparation for racial bias messages (e.g., racial barriers) may enable youth to cope with racial discrimination through their increased knowledge of history and ability to attribute a racist encounter to an external source instead of internalizing that racism (Hughes et al, 2006). However, contrary to their predictions, Dotterer and James (2018) found that preparation for racial bias exacerbated the effect of racial discrimination on African American adolescents’ depressive symptoms. Greater awareness of the existence of racial bias in society could influence youth’s expectations of persistent racial discrimination and unfair treatment.…”
Section: Racial Discrimination Experiences Among African American Adomentioning
confidence: 83%
See 1 more Smart Citation
“…Among the 69 studies that examined links between preparation for bias and youth adjustment, many reported null associations (e.g., Atkin et al, ; Else‐Quest & Morse, ; Ferrari, Ranieri, Barni, & Rosnati, ; French & Coleman, ; Tran & Lee, ), a few reported both positive and negative effects (e.g., Kyere & Huguley, ), and a few found preparation for bias to be associated with increased risk (e.g., Daga & Raval, ; van Bergen, Ersanilli, Pels, & De Ruyter, ). In terms of risk, some studies found that preparation for bias directly predicted greater maladjustment such as higher depressive symptoms (e.g., Liu & Lau, ; Nelson et al, ), whereas other studies found that it exacerbated the negative effect of stressors on adjustment (e.g., Banerjee, Rowley, & Johnson, ; Dotterer & James, ). In contrast, other studies found preparation for bias to be promotive for youth either because it was directly associated with indicators of positive youth outcomes (e.g., D'hondt, Eccles, Van Houtte, & Stevens, ; Joseph & Hunter, ; Sanchez, Smith, & Adams, ), it reduced the negative effects of risk on youth adjustment (e.g., Schires et al, ), or it enhanced the positive effects of other promotive factors on youth adjustment (e.g., Tran & Lee, ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…As a result, researchers are demanding the need to study ethnic identity in other countries around the world, realizing that empirical research in the USA should not self-evidently be applied to other societies and used as the frame of reference for the field (Verkuyten, 2016). Besides identity concerns adolescents have to deal with (such as occupation, ideology, and gender roles), ethnic minority adolescents have to face other aspects derived from being a member of a group that is typically of lower status and power in society and that may be subject to discrimination (Dotterer & James, 2018).…”
Section: Introductionmentioning
confidence: 99%